Socialization of Organic Waste Processing Using Composter Drum at SMAN 67 Jakarta - Sungkono Sungkono; W. Tedja Bhirawa; Basuki Arianto; Hari Moektiwibowo; Ersha Mayori (International Journal of Social Science and Community Service, 2025)
Waste is a form of problem that needs to be managed and carried out in an integrated manner from upstream to downstream so as not to cause environmental pollution. As part of the AdiwiyataSchool, SMAN 67 Jakarta has several working groups (pokja) including the Wast e Pokja, CompostPokja, and Hydroponic Pokja. However, the available solid compost fertilizer production facilities have not been optimally utilized and the working groups that are run have not run according totheir goals. The aim of this PKM activity is to educate students on the significance of converting waste into useful products, enhance the skills of teachers and students in making compost fertilizers, and support the Adiwiyata School program at SMAN 67 Jakarta. The target of thisactivity is the teachers and students of SMAN 67 Jakarta, especially those who are members of theCompost Pokja. The PKM implementation method consists of four stages: (1) Survey and analysis of partner needs, (2) Lecture-based material delivery, (3) Hands-on practice in processing organic waste into solid and liquid compost fertilizers, and (4) Evaluation based on participants' understanding of the material. The results of this PKM activity are as follows: (1) Participants' knowledge of waste processing into higher-value derivative products improved, as evidenced by an increase in pre-test and post-test scores from 79.45 to 85.04; (2) Participants developed skills in producing solid and liquid compost fertilizer for integration into the work program; (3) A composter drum was donated to SMAN 67 Jakarta to support its Adiwiyata School program.